Pengaruh Good Corporate Governance Terhadap Tax Avoidance - Rizky Ridwan; Retno Dyah Pekerti (JURNAL EKONOMI PERJUANGAN, 2022)
This research was a descriptive and explanatory research, using data panel regression analysis. The software used in analyzing the data was Eviews 9. The data analysis in this study started with model testing with the approach of Common Effect Model, Fixed Effect Model and Effect Model; and the model selection testing was conducted through Chow, Hausman, and Langgage Multiplier tests. It was then followed by classic assumption test that comprised of normality test, heteroscedasticity, autocorrelation and multicollinearity tests. Then, the data panel regression test and hypothesis testing were done in form of partial regression coefficient (t test) and determination coefficient test. The populations in this research were about 90 reports of financial data, while the samples were about 30 reports with the criteria of the companies were being the participants in the Corporate Governance Perception Index (CGPI) and had annual report and sustainability continuously. The data in this study were secondary, obtained by data collection technique of documentation method and literature study. This research showed that the Managerial Ownership had positive and significant impact on the Tax Avoidance, while the Independent Commissioner and Institutional Ownership did not influence significantly on the Tax Avoidance. Keywords : CGPI